Deconstructing Myths in Osama Hajjaj Caricatures: Semiotic Analysis of the Israel-Palestine Conflict on Instagram - Santika, R. Gilang; Rohanda, Rohanda; Supianudin, Asep (Universitas Yudharta Pasuruan, 2025)
The Israel-Palestine conflict is a global issue laden with power dynamics, ideological struggles, and media representation. Amid dominant and often biased global narratives, visual works such as political caricatures offer an alternative space for voicing criticism and solidarity. This study aims to uncover both the denotative and connotative (mythological) meanings within digital caricatures by Osama Hajjaj, published through his Instagram account. Using a qualitative descriptive method and Roland Barthes’ semiotic approach, which distinguishes between the levels of denotation and connotation. This research analyzes five purposively selected caricatures that explicitly portray the Israel–Palestine conflict, rich in symbolic and contextual relevance (October–December 2024). The findings reveal that at the denotative level, the caricatures depict the realities of conflict through visual elements such as military aggression, civilian suffering, and international institutions. At the connotative level, they deconstruct ideological myths, including digital solidarity, the illusion of ceasefire, the war on terrorism, the hypocrisy of power, and the impartiality of international organizations. These caricatures function as a form of symbolic resistance that not only conveys information but also shapes public consciousness and critiques global power structures. As such, Osama Hajjaj’s works serve as visual texts that play a significant role in the construction and deconstruction of meaning surrounding the Israel–Palestine conflict in the digital age.